2007
DOI: 10.1007/s10433-007-0057-1
|View full text |Cite
|
Sign up to set email alerts
|

Promoting physical activity in older adults by education of home visitors

Abstract: The objectives were to investigate in older adults (1) whether regular preventive home visits are associated with change or stability in physical activity and (2) whether education of home visitors influences stability and change in physical activity. The design was a prospective controlled randomised follow-up study with randomization at municipality level (17 intervention and 17 control municipalities) and outcomes measured at individual level. Visitors in the intervention-municipalities received regular edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Ten studies [ 47 50 , 52 57 ] used a longitudinal design with at least one before and one after measurement. Among these, six [ 47 , 52 55 , 57 ] included a control group and therefore had the highest suitability of study design. The remaining four studies [ 48 – 50 , 56 ] used a single group pre-post design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies [ 47 50 , 52 57 ] used a longitudinal design with at least one before and one after measurement. Among these, six [ 47 , 52 55 , 57 ] included a control group and therefore had the highest suitability of study design. The remaining four studies [ 48 – 50 , 56 ] used a single group pre-post design.…”
Section: Resultsmentioning
confidence: 99%
“…This study could not be evaluated concerning its suitability since none of the four categories included in the scale of suitability of study design captured its design features adequately. Three studies [ 51 53 ] met five of the six quality criteria, four studies [ 49 , 54 , 55 , 57 ] met four, three studies [ 48 , 50 , 56 ] met three, and the remaining study [ 47 ] met two quality criteria (Additional file 3 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of them present functional outcome data extended out to the 4.5-year follow-up [one on general functional decline patterns (Vass et al 2007a, b), and another on physical activity (Poulsen et al 2007)]. A third paper examines another secondary outcome ''tiredness in daily activities'' ).…”
Section: This Issue's Papersmentioning
confidence: 97%
“…Analyses were conducted with SPSS version 15.0 and included Pearson's chi-square test, bi-and multivariable logistic regression analyses with a significance level of 5%. Several studies have indicated that gender is an effect-modifier (Poulsen et al 2007, Avlund et al 2008). Hence, the multivariable logistic regression analyses were stratified by sex.…”
Section: Statistical Analysesmentioning
confidence: 99%